Fabrication, characterisation and dielectric properties of KH550 modified BST/PVDF nanocomposites with high dielectric strength - Li Wang; Feng Gao; Jie Xu; Kena Zhang; Min Wang; Mengjie Qin (High Voltage, 2016)
Ba(0.6)Sr(0.4)TiO(3) (BST)/poly(vinylidene fluoride) (PVDF) 0–3 nanocomposites with BST nanoparticle contents of 10–40 vol% were prepared by tape casting method. The BST nanoparticles with ∼60 nm crystal size and accurate atomic ratio were synthesised by sol–gel method. The effect of the BST nanoparticle contents on the microstructure and dielectric properties of BST/PVDF nanocomposites were investigated. The BST/PVDF nanocomposites system declares that feasibility of applying low contents nanoparticles to form a homogeneous distribution in polymer matrix, higher dense interface connectivity, thereby providing a significant improvement to the dielectric strength and energy storage density; meanwhile, the nanocomposites possess high dielectric tunability. In this study, the maximum dielectric strength ∼287.12 kV/mm and energy storage density ∼5.15 J/cm^3 were obtained in 10 vol% BST/PVDF nanocomposites, respectively. Moreover, the nanocomposite possesses high dielectric tunability ∼62.6% at 58 kV/mm, which proposed the nanocomposites suitable for tunable microwave devices, supercapacitors and energy storage device applications at high-voltage environment.